Influence of Human Sera on the In Vitro Activity of the Echinocandin Caspofungin (MK-0991) against Aspergillus fumigatus - Chiller, Tom (American Society for Microbiology, 2000)
There have been several reports that the activity of echinocandin antifungal agents is not affected or decreased in the presence of human sera. It is known that these drugs are bound >80% in animal and human sera. The activity of the echinocandin caspofungin (MK-0991), a 1,3-β-d-glucan synthase inhibitor, against Aspergillus fumigatus with and without human sera was studied. Conidia of A. fumigatus in microtest plate wells formed germlings after overnight culture in RPMI 1640. Caspofungin was then added with or without serum, and the germlings were incubated at 37°C for 24 h. Human serum (5%) in RPMI 1640 alone did not significantly inhibit the growth of A. fumigatus in vitro. Caspofungin in RPMI 1640 exhibited dose-dependent inhibition, with concentrations of 0.1 and 0.05 μg/ml inhibiting 24.9% +/− 10.4% and 11.7% +/− 3.6%, respectively (n = 10; P < 0.01). The addition of 5% human serum to caspofungin at 0.1 or 0.05 μg/ml increased the inhibition to 78.6% +/− 5.8% or 58.3% +/− 19.2%, respectively (n = 10; P < 0.01 versus controls and versus the drug without serum). Lower concentrations of serum also potentiated drug activity. The effect of human sera was further seen when using caspofungin that had lost activity (e.g., by storage) against A. fumigatus at 0.1 μg/ml. Inactive caspofungin alone demonstrated no significant inhibition of hyphal growth, whereas the addition of 5% human serum to the inactive drug showed 83% +/− 16.5% inhibition (n = 5; P < 0.01). The restoration of activity of caspofungin was seen at concentrations as low as 0.05% human serum. In contrast to prior reports, this study suggests that human serum acts synergistically with caspofungin to enhance its inhibitory activity in vitro against A. fumigatus.